Potensi Filtrat Daun Salam Sebagai Bioinsektisida Lalat Rumah Dengan Metode Efikasi Aerosol Tahun 2021 - CHANDRA BAGASKARA CHANDRA BAGASKARA PUTRA; NGADINO NGADINO; SETIAWAN SETIAWAN (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
House flies (Musca domestica) are one of the vectors of disease that can be found around. The potential of various kinds of diseases carried by house flies is the reason why the efforts to contol this vector is quite important, one of which is the use of bioinsecticides. This study was aimed to determine the potential of salam leaf filtrate (Syzygium polyanthum) as bioinsecticide for house flies.This research is categorized as an experiment with a Posttest-Only Control Group Design type with a concentration of 7.5%, 10%, 15%, control and 6 times replication. Data were analyzed using One Way Anova, Two Way Anova, and probit analysis.The results was showed p